Terrestrial Ecoregions of the Indo Pacific A Conservation Assement - Wikramanayake Eric (Island Press, 2002)
This book, along with its companions in this series, takes an ecoregional approach, dividing large regions into small, distinct units, each with its characteristic species, ecosystems, natural history, and threats. As such, it has no peers. It is the sourcebook for anyone who must look for where and how to act to save the variety of life on Earth." - from the foreword by Stuart L. Pim.